2018
DOI: 10.1007/s11883-018-0739-5
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Autoregulation in Stroke

Abstract: Existing data suggest that CA is generally impaired in various cerebrovascular disorders. In patients with small vessel ischemic stroke, CA has been shown to be impaired in both hemispheres, whereas in large territorial strokes, CA impairment has been limited to the affected hemisphere. In these latter patients, impaired CA is also predictive of secondary complications such as hemorrhagic transformation and cerebral edema, hence worse functional outcome. In patients with carotid stenosis, impaired CA may also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 104 publications
0
92
0
2
Order By: Relevance
“…To address this gap in knowledge, we performed a systematic review of the literature, including meta-analyses of gain, phase and ARI in studies of both ischemic and hemorrhagic stroke. Although some recent reviews have made reference to the application of TFA in studies of stroke, 5,15,16 to our knowledge, this study is the first to perform a systematic review of this topic, with meta-analyses of gain, phase and ARI.…”
Section: Introductionmentioning
confidence: 99%
“…To address this gap in knowledge, we performed a systematic review of the literature, including meta-analyses of gain, phase and ARI in studies of both ischemic and hemorrhagic stroke. Although some recent reviews have made reference to the application of TFA in studies of stroke, 5,15,16 to our knowledge, this study is the first to perform a systematic review of this topic, with meta-analyses of gain, phase and ARI.…”
Section: Introductionmentioning
confidence: 99%
“…CA has been shown to be affected in disease states such as stroke (Xiong et al, 2017), Alzheimer's disease (Claassen, Diaz-Arrastia, et al, 2009) and traumatic brain injury (Bor-Seng-Shu et al, 2012). Additionally, impaired CA postischemic stroke has been demonstrated as an independent predictor of outcome and secondary complications, such as hemorrhagic transformation and cerebral oedema (Castro, Azevedo, & Sorond, 2018;Castro, Serrador, Rocha, Sorond, & Azevedo, 2017;Chi et al, 2018). Therefore, individualized hemodynamic management may be a key to improving clinical outcomes in stroke patients (Castro et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In yet another study, these authors reported that final infarct volume is significantly lower in patients with preserved autoregulation in a similar acute window post-stroke (41). In a review summarizing these findings, Castro et al conclude that early autoregulatory measures wield considerable import in the guidance of acute stroke management, secondary injury prevention, and outcome improvement (35).…”
Section: Cerebral Autoregulation and Blood Pressure Personalizationmentioning
confidence: 97%
“…Furthermore, in stroke patients with impaired autoregulation, recovery tends to be delayed for up to 3 months, underlining the clinical relevance of autoregulation in stroke research (35,39). That said, only a handful of studies have looked at functional outcome prognostication with respect to autoregulation physiology in stroke.…”
Section: Cerebral Autoregulation and Blood Pressure Personalizationmentioning
confidence: 99%